The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.4269/ajtmh.2002.67.436
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatitis C infection in chronic liver disease in Egypt.

Abstract: Abstract. Hepatitis C virus (HCV) is considered the most common etiology of chronic liver disease (CLD) in Egypt, where prevalence of antibodies to HCV (anti-HCV) is ∼ 10-fold greater than in the United States and Europe. Reported are results that show the role of HCV in both overt and occult CLD, the risk factors for CLD and for HCV infection, and the relative importance of chronic HCV, hepatitis B, or both in causing hepatic morbidity. Case patients included 237 new outpatients at the National Liver Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 40 publications
6
73
0
Order By: Relevance
“…A case-control study that compared 237 outpatients seen at the National Liver Institute (cases) with 212 gender-and age-matched neighbors who denied liver disease (controls) supported this belief that HCV is the predominant cause of liver disease and that there is a large occult reservoir of HCV-caused chronic liver disease in the country. 26 Others also reported that HCV infection with genotype 4a was the main cause of chronic liver disease in 135 adult patients living in Alexandria 27 and in 801 residents of a Nile Delta community. 28 Case-control studies have shown that both HBV and HCV infection increase the risk of HCC (adjusted odds ratios of [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Magnitude Of Hcv-caused Chronic Liver Disease In Egyptmentioning
confidence: 99%
“…A case-control study that compared 237 outpatients seen at the National Liver Institute (cases) with 212 gender-and age-matched neighbors who denied liver disease (controls) supported this belief that HCV is the predominant cause of liver disease and that there is a large occult reservoir of HCV-caused chronic liver disease in the country. 26 Others also reported that HCV infection with genotype 4a was the main cause of chronic liver disease in 135 adult patients living in Alexandria 27 and in 801 residents of a Nile Delta community. 28 Case-control studies have shown that both HBV and HCV infection increase the risk of HCC (adjusted odds ratios of [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Magnitude Of Hcv-caused Chronic Liver Disease In Egyptmentioning
confidence: 99%
“…[6][7][8] HCC is the second most frequent cause of cancer incidence and mortality among men in Egypt. 9 Hospitalbased studies from Egypt have reported an increase in the relative frequency of all liver-related cancers in Egypt (>95% as HCC), from 4.0% in 1993 to 7.3% in 2003.…”
mentioning
confidence: 99%
“…Though all patients who developed this side effect were hepatitis C positive, this could hardly been seen as a cause and effect relationship. Hepatitis C is known to be endemic in Egypt where prevalence of antibodies to HCV (anti-HCV) is approximately tenfold greater than in the United States and Europe (20). Hence, a substantial percentage of patients in this material are expected to be hepatitis C positive.…”
Section: Discussionmentioning
confidence: 99%